Stale examination of plant varieties fitoenergetk directly using - Д. Б. Рахметов; А. В. Андрющенко; К. М. Кривицький; В. В. Мамайсур (Plant Varieties Studying and Protection)
In the article are submitted of bioenergy developments in the world and is provided rating of various types of plants for use in the fitoertergetics. Expresd one’s opinion about criteria descriptions of varieties relatively fitoenergetic using.